Development and psychometric properties of the client's assessment of treatment scale for supported accommodation (CAT-SA). Issue 1 (December 2016) - Sandhu, Sima; Killaspy, Helen; Krotofil, Joanna; McPherson, Peter; Harrison, Isobel; Dowling, Sarah; Arbuthnott, Maurice; Curtis, Sarah; King, Michael; Leavey, Gerard; Shepherd, Geoff; Priebe, Stefan
Abstract Background Patient-Reported Outcome Measures (PROMs) are important for evaluating mental health services. Yet, no specific PROM exists for the large and diverse mental health supported accommodation sector. We aimed to produce and validate a PROM specifically for supported accommodation services, by adapting the Client's Assessment of Treatment Scale (CAT) and assessing its psychometric properties in a large sample. Methods Focus groups with service users in the three main types of mental health supported accommodation services in the United Kingdom (residential care, supported housing and floating outreach) were conducted to adapt the contents of the original CAT items and assess the acceptability of the modified scale (CAT-SA). The CAT-SA was then administered in a survey to service users across England. Internal consistency was assessed using Cronbach's alpha. Convergent validity was tested through correlations with subjective quality of life and satisfaction with accommodation, as measured by the Manchester Short Assessment of Quality of Life (MANSA). Results All seven original items of the CAT were regarded as relevant to appraisals of mental health supported accommodation services, with only slight modifications to the wording required. In the survey, data were obtained from 618 clients. The internal consistency of the CAT-SA items was 0.89. Mean CAT-SA scores were correlated with the specific accommodation item on the MANSA (r s = 0.37, p ˂.001). Conclusions The content of the CAT-SA has relevance to service users living in mental health supported accommodation. The findings from our large survey show that the CAT-SA is acceptable across different types of supported accommodation and suggest good psychometric properties. The CAT-SA appears a valid and easy to use PROM for service users in mental health supported accommodation services.